Why We Gesture : The Surprising Role of Hand Movements in Communication - McNeill, David (Cambridge : Cambridge University Press, 2015)
Gestures are fundamental to the way we communicate, yet our understanding of this communicative impulse is clouded by a number of ingrained assumptions. Are gestures merely ornamentation to speech? Are they simply an'add-on' to spoken language? Why do we gesture? These and other questions are addressed in this fascinating book. McNeill explains that the common view of language and gesture as separate entities is misinformed: language is inseparable from gesture. There is gesture-speech unity. Containing over 100 illustrations, Why We Gesture provides visual evidence to support the book's central argument that gestures orchestrate speech. This compelling book will be welcomed by students and researchers working in linguistics, psychology and communication.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).